KRALICEK QUICK TEST – AN ANALYSIS TOOL FOR ECONOMIC UNITS DETERMINATION IN LIABILITY DIFFICULTY - Polo, Antoneta; Caca, Enkela (European Scientific Journal, ESJ, 2014)
Reports are very necessary profitable tools in financial analysis that help financial analysts in the submission of the plans to improve profitability, liability, financial structure, reorganization, financial levers and interest coverage. Even though reports indicate more than last performances, they might be very predictable to ensure important indicators in the analysis of problems. Their intention is to feed economic units with valuable information in the general leading. Practical value of the reports lies upon the fact that two data, which are isolated from each other but each preserves its internal value, might gain a specific interest when being studied not in an isolated way but in the way of a comparison or relation. In this article, we have tried to highlight the role of analysis through financial reports in the prediction of paying difficulties. A very important tool in this direction is the Kralicek Quick Test. The reached consideration demonstrates weak sides of economic units and helps to reach the conclusion that which of the indicator groups can affect negatively in the general level of paying ability. By using Kralicek Quick Test, it becomes possible to determine the indication of two factor groups such as financial stability and efficiency with the meaning of consideration of financial state.